SURGICAL MANAGEMENT OF INTESTINAL DISORDERS THROUGH LEFT FLANK LAPAROTOMY IN BOVINE – A REVIEW OF SIX CASES - R. S. Vijayaboorani; K. Jayakumar; S. Senthil Kumar; S. Sivagnanam (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Six cattle presented with history and clinical signs pertaining to intestinal disorders requiring surgical intervention were subjected to left flank laparotomy. The animals were clinically examined and stabilized with fluid therapy before performing exploratory laparotomy. Left flank laparotomy was performed under Farquharson’s paravertebral nerve block in standing position. The efficacy of surgery through left flank to intestinal affections was evaluated by ease of approach, accessibility and visceral pain. It was found that caudal left flank approach allowed more ease of exteriorization of intussuscepted masses that were in jejunum, jejuno-jejunum, ileum and ileo-caecal parts of the intestine and also allowed complete exploration of the abdominal cavity. Left flank laparotomy approach with or without rumenotomy resulted in more area of exploration, prevented the proximal distended intestines to spill out and specific exteriorisation of the affected segment, by which mesenteric pain was alleviated that otherwise leads to recumbency and kicking at abdomen by the animals which could result in multiple rupture of intestines.